2015
DOI: 10.4274/tjo.45722
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Vision Loss after Delivery in Two Cases: Severe Preeclampsia and HELLP Syndrome

Abstract: Two patients with no symptoms of hypertension in their medical history before pregnancy were referred to the obstetrics emergency clinic with hypertension and visual complaints. After physical examination and laboratory tests, one of the patients was diagnosed with severe preeclampsia while the other was diagnosed with HELLP syndrome (Hemolysis-Elevated Liver enzymes-Low Platelets). Ocular examinations were performed after delivery due to the patients’ worsening visual complaints. The severe preeclamptic patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“… 7 12 13 It has been shown that preeclamptic women complicated by HELLP (Haemolysis, Elevated Liver enzymes and Low Platelets) syndrome are seven times more likely to develop retinal detachment than those who do not develop HELLP. 14 …”
Section: Introductionmentioning
confidence: 99%
“… 7 12 13 It has been shown that preeclamptic women complicated by HELLP (Haemolysis, Elevated Liver enzymes and Low Platelets) syndrome are seven times more likely to develop retinal detachment than those who do not develop HELLP. 14 …”
Section: Introductionmentioning
confidence: 99%
“…The most common OCT finding is the elevation of the inner and outer retinal layers associated with severe neurosensorial retinal detachment as well as intraretinal cysts. [ 13 ] In our case, there was severe neurosensorial retinal detachment in the right eye but there were no intraretinal cysts.…”
Section: Discussionmentioning
confidence: 54%
“…In line with the literature, we observed that SRD gradually resolved, and visual acuity recovered completely. 13 , 14 …”
Section: Discussionmentioning
confidence: 99%